Movement forward on ABS for the Convention on Biological Diversity: Bounded openness over natural information - Joseph H. Vogel; Manuel Ruiz Muller; Klaus Angerer; Christopher May (South Centre, 2022)
Access to genetic resources and "fair and equitable sharing of benefits arising [from their] utilization" is the third objective of the 1992 United Nations Convention on Biological Diversity (CBD). The expression is included in the full title of the 2010 Nagoya Protocol (NP). Neither agreement defined "material" in the phrase "genetic material" which resulted in misinterpretation that the object of access for R&D is tangible. Unfairness ensues: competition among provider Parties leads to the elimination of economic rents, which is desirable for tangibles but undesirable for intangibles. Once interpreted as natural information, the economics of information justifies a Global Multilateral Benefit-Sharing Mechanism (GMBSM) (Article 10 NP) which collects and distributes rents on value added to genetic resources. "Bounded openness over natural information" is the modality proposed for the GMBSM. The Executive Secretary of the United Nations Secretariat of the CBD recognized the argument in the 2021 Note "Digital Sequence Information on Genetic Resources".
Keywords: 300; Access and Benefit-Sharing (ABS); Bounded Openness; Convention on Biological Diversity (CBD); Digital Sequence Information (DSI); Genetic Resources; Global Multilateral Benefit-Sharing Mechanism (GMBSM); Intellectual Property Rights (IPRs); Nagoya Protocol; Natural Information; Research and Development (R&D); TRIPS; United Nations Framework Convention on Climate Change (UNFCCC)